A Pilot Study of a Hybrid Process Involving In Situ Regenerated Activated Carbon, Membrane Separation and Advanced Oxidation for Water Pollution Abatement - Sarasidis, Vasilis C.; Plakas, Konstantinos V.; Karabelas, Anastasios J. (Journal of Chemical Engineering Research Updates, 2021)
The assessment of a pilot-scale hybrid system coupling powdered activated carbon (PAC) adsorption with membrane ultrafiltration (UF), in respect of activated carbon regeneration and organic micropollutant removal, was investigated in this study. Field tests with two adsorbents (i.e. a commercial PAC and a PAC-Fe(II) composite), conducted in the premises of Thessaloniki Water Treatment Plant, demonstrated the high efficiency of the combined PAC/UF process. Regeneration efficiencies varying between approximately 95% and 110%, complete diclofenac (DCF) degradation and rather moderate mineralization (TOC removal) rates of up to 47%, can be achieved by UVC/H2O2 or photo-Fenton oxidation after 4 hours of treatment; this performance is attributed to the in situ generation of reactive oxidant species by photolysis of H2O2, which seems to enhance the process effectiveness. Among the two adsorbent materials tested, composite PAC-Fe(II) exhibited a higher DCF adsorption capacity than the original PAC, probably due to the improved chemisorption and/or the electrostatic attractive interactions between the negatively charged DCF molecules and the positively charged iron species, at neutral pH. Furthermore, a rather insignificant effect of PAC-Fe(II) loading on the regeneration efficiency was observed. The advantages of totally controlled H2O2 dosages and short operating times render the hybrid PAC/UF system a promising alternative to conventional and advanced drinking water purification methods.